The Trainability of Explosive Power Features and Their Negative Correlation with Body Fatness in Collegiate American Football Players - Erkan Akdoğan; İsmail Bayram and Ali Onur Cerrah (Journal of Educational Issues, 2024)
Both sports education and training interventions create a dose-response relationship in the body which change the body composition. The aim of this study is to investigate the relationship between pre-season body composition and physical performance parameters of collegiate American football players. 23 American football players (age: 22.3±3.1 years, height: 180.6±5.6 cm, weight: 94.2±16.9 kg) voluntarily participated in the study. The body compositions of players were determined via Dual-Energy X-ray Absorptiometry (DEXA) device and countermovement jump (CMJ), 10 and 40-yard sprinting and pro-agility tests were applied to evaluate physical performance. Pearson Correlation analysis was used to determine whether there was a relationship between body composition parameters and field tests. As a result, a statistically significant negative correlation (p < 0.05) was found between body fat percentage (r = -.736; p < .001) and body fat mass (r = -.717; p < .001) with CMJ. A statistically significant relationship (p<0.05) was found between body fat percentage (r = .622; p < .002; r = -.759; p < .001) and body fat mass (r = .595; p < .003; r = -.736; p < .001) with 10 and 40-yard sprints respectively. Body fat percentage (r = .659; p < .001) and body fat mass (r = .638; p < .001) also correlated with pro-agility. Our results support earlier research by showing a direct correlation between body composition and power attributes and performance in American football. Coaches were advised to pay attention to body adiposity in terms of a decline in physical performance for this reason.